2014
DOI: 10.1111/pcmr.12242
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the intrinsic apoptosis pathway as a strategy for melanoma therapy

Abstract: Summary Melanoma drug resistance is often attributed to abrogation of the intrinsic apoptosis pathway. Targeting regulators of apoptosis is thus considered a promising approach to sensitizing melanomas to treatment. The development of small‐molecule inhibitors that mimic natural antagonists of either antiapoptotic members of the BCL‐2 family or the inhibitor of apoptosis proteins (IAPs), known as BH3‐ or SMAC‐mimetics, respectively, are helping us to understand the mechanisms behind apoptotic resistance. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 163 publications
(236 reference statements)
0
48
0
Order By: Relevance
“…Induction of apoptosis by anti-cancer drugs is preferred since those that cause necrosis can elicit excessive non- specific cellular/tissue destruction [47]. After we found that P1 and P2 induce apoptosis, additional assays were performed to determine whether P1 and P2 may induce cell death via the intrinsic apoptotic pathway [48] and, indeed, we found that treatment with P1 and P2 resulted in impairment of mitochondrial membrane potential. A final step in apoptosis is activation of the executioner caspase-3.…”
Section: Discussionmentioning
confidence: 98%
“…Induction of apoptosis by anti-cancer drugs is preferred since those that cause necrosis can elicit excessive non- specific cellular/tissue destruction [47]. After we found that P1 and P2 induce apoptosis, additional assays were performed to determine whether P1 and P2 may induce cell death via the intrinsic apoptotic pathway [48] and, indeed, we found that treatment with P1 and P2 resulted in impairment of mitochondrial membrane potential. A final step in apoptosis is activation of the executioner caspase-3.…”
Section: Discussionmentioning
confidence: 98%
“…The capability of evading apoptosis is critical for the developments and sustained growths of many, perhaps all, cancers, and the induction of apoptosis has now been considered as an important approach for cancer therapy [25,26]. It is currently known that two major pathways including intrinsic and extrinsic apoptotic signalings are involved in the regulation of apoptosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…NOXA and BIM play important roles in antagonizing MCL-1 and BCL-2 in melanoma 1,2 , and we have previously found that NOXA and BIM are crucial at inducing cell death when ABT-737 (an earlier version of ABT-263) was used in combination with other agents 2,5,1921,35,46 . Immunoblots showed that the combination treatment increased the expression of NOXA and BIM in some of the lines (Supplementary Figure 4a and Supplementary Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Upregulation of anti-apoptotic BCL-2 family members contribute to tumorigenesis, and resistance to chemotherapy and molecular-targeted therapies 1,2 . BH3 mimetics represent a novel class of cancer therapeutic drugs, which directly activate apoptosis by binding and inhibiting anti-apoptotic BCL-2 family members, thus bypassing the requirement for upstream initiators, such as p53 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation